A mirror garden - Shahroudy Farmanfarmaian, Monir 1922-2019; Houshmand, Zara (Anchor Books, 2008)
"In Persia in 1924, when a child still had to worry about hostile camels in the bazaar and a nanny might spin stories at her pillow until her eyes fell shut, the extraordinary and irresistible Monir Shahroudy Farmanfarmaian was born. From the enchanted basement storeroom where she played as a girl to the penthouse high above New York City where she would someday live, this is the delightful and inspiring story of her life as an artist, a wife and mother, a collector, and an Iranian"--P. [4] of cover.